Efektivitas Pengendalian Gulma Tanaman Eucalyptus sp pada Areal Mineral di Estate Cerenti, PT. RAPP - Triwiharto, Agung; Yuslinawari; Prijono, Agus; Asmar, Dika (Jurnal Wana Tropika, 2022)
One of the wood industry activities in the forestry sector is the Eucalyptus sp industry at PT.Riau Mainstay Pulp and Paper Riau Province. The wood production process is used for pulpand has many factors in its productivity. One of them is in the planting process with weedcontrol problems, which use the herbicide with the active ingredient glyphosate. The use of the herbicide with the active ingredient glyphosate is not effective against all types of weeds. Therefore, it is necessary to know the right combination of weed control methods to control weeds for the expected results. Research is located in PT. RAPP, Kuantan Singingi Regency, Riau Province. The research design used was a completely randomized design with a factorial pattern that used 2 treatment factors in the form of Weeding Round consisting of Weeding Round 5 Over Due (late weeding) and Weeding Round 5 On Time (on time) and weed control methods consisting of chemical methods, the tripe combination method with chemical and thecombination lever method with chemical. The parameters observed were the type and amount of weed vegetation, the development of weed death, the percentage of weed death and the PQA value of weeding. Data were analyzed by analysis of variance. The results that showed a significant effect were further tested using the LSD (Least Significant Difference) test. The results showed that there were 6 types of weeds found in the research area, namely Senduduk Bulu (Clidemia hirta), Senduduk (Melastoma malabathricum), Acacia mangium saplings (Acacia mangium), Lemidi Paku (Stenochlaena palustris), Grass (Poaceae) and Liana. The most dominant type of weed was Clidemia hirta with an Important Value Index of 127.72% and the weed with the smallest effect was liana with an Important Value Index of 0.88%. Based on the results of the analysis of the development of weed mortality, the percentage of weed mortality and the PQA value of weeding, the combination of jackhammer and chemical method is the most appropriate control method applied because it has an average PQA value of 100%.In the chemical method there are fern weeds that are difficult to die and in the combination tripe and chemical method there are fern weeds that grow new leaves on the 16th day of observation.Keywords: PQA Weeding; Weeds; Weed Control Methods